Corporate crime in the pharmaceutical industry: why we must be concerned - Azlinda Abdul Samad,; Abdul Samad Abdul Ghani, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The impact of corporate crime is wide and varies. This study intends to highlight on this, from the perspective of the pharmaceutical industry. This study is conducted by using a semi-structured interview question. Information is also collected from books, journals, reports, websites etc. The objective of this study is to determine the impacts of corporate crime in the pharmaceutical industry and provides some suggestion to overcome the issues. Corporate crime in the pharmaceutical industry is an issue of concern because of its impact, especially on public safety and health, as it may lead to serious cases of permanent disability and fatality. Additionally, it can lead to other serious issues including the diversion of prescription medicine for non-medical or illicit use. It may also hamper the nation with the issue of drug problems which will consequently, affect the family institution as well as the society at large. The health system may also be affected due to the unsafe use of medicinal products and unethical practices among health professionals and personnel. Consumers or patients may also be exposed to untruthful and inaccurate drug advertisements and information. The crime has a negative impact on the pharmaceutical company itself and may tarnish the country’s name and reputation. To overcome and stop corporate crime, requires cooperation and commitment from various entity. Holistic actions and approaches need to be taken to dealt with the issue immediately so it does not get worse.